BirthChain: a blockchain platform for birth certificates - Sapra, Riya; Ul Rehman, Shafiq; Malhotra, Sugandhi; Arora, Shraddha; Dhaliwal, Parneeta (Frontiers in Blockchain, 2026)
Blockchain is the evolving technology used by government and private organizations to empower themselves by digitizing and automating their work with the help of distributed computing and cryptography. This technology is being adopted by numerous application areas, including land registry, notarization, civil registration system, and digital certification. In this article, a blockchain-based platform called BirthChain is proposed for digitizing the birth certificate generation and distribution process. Hospitals will use this platform to provide data on newborns, which will be validated by the municipal corporations. The birth certificates will be automatically generated and emailed to the parents in addition to the existing process of certificate generation and handling. The platform will streamline the current birth certificate generation process, remove delays, and provide a secure digital platform. BirthChain has been implemented using Ethereum’s Remix IDE. BirthChain is validated by discussing its implementation on various Ethereum Virtual Machine (EVM)-compatible blockchain networks and comparing it to the existing birth certificate generation process.